Government interventions in supporting SME growth in Lira district, northern Uganda - Eton, Marus (International Journal of Emerging Research & Development, 2018)
Promoting economic growth without attendance to register business time, business education investment and non-gender based business growth is outrageous. The study sought to examine the role of Government interventions in supporting the growth of SME’s in Uganda a case of Lira District. Data were collected by use of the self-administered questionnaire in Erute counties and Lira Municipality. A sample of 167 respondents was chosen from the respondents and the response rate was 100%. Simple random sampling and stratified sampling was conducted. The study discovered that inadequacy of collateral security and struggle for financial resources come into view to limit the use and access to financial services. The finding indicates the correlations between entrepreneurship intervention and financial accessibility intervention (r = .628; p < .05) was relatively strong and statistically significant. The study recommended that Government should promote collateral security-free financial services to encourage entrepreneurs to access credit financing. The government organ charged with registration of business should promote online and decentralized registration. National budgets should prioritize investments in business education to promote business and entrepreneurship training. In addition, government and development partners should promote non-gender-based business growth to allow for participatory inclusiveness.